Screen-Based Emotion Regulation in Early Childhood Parenting: A Systematic Literature Review and Bibliometric Analysis - Khairati, Zulfa; Agustan; Hikmatur Rahmah; Hildawati; Rohmah, Lailatu; Muammar Qadafi (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2026)
Mobile devices are increasingly used to calm, distract, or manage young children, a practice described as the digital pacifier. Although widely discussed in digital parenting research, the phenomenon remains diffuse because it is approached through adjacent constructs rather than through a clearly defined framework. This study examined how the digital pacifier is represented across the literature and whether it is better understood as an isolated parenting tactic or as part of a broader relational process. A two-stage review design combined bibliometric mapping with a systematic literature review. Bibliometric analysis used Scopus-indexed records, followed by a PRISMA-guided review of studies from Scopus, ScienceDirect, and Google Scholar, resulting in a final corpus of 25 studies. The findings show that the literature is growing but remains fragmented. Across the reviewed studies, a pattern links reactive, stress-related device use to parental strain, technoference, and less favorable developmental conditions, especially when device use weakens responsiveness and interrupts co-regulatory interaction. The evidence does not support a uniform risk narrative, because outcomes vary by child characteristics, device type, context of use, and parental mediation. The review therefore argues that the digital pacifier is better understood as a relational and context-sensitive process rather than as a simple screen-time problem. Its main contribution lies in clarifying this pattern through the interpretive framework of the Digital Pacifier Cycle while also showing that the model remains provisional and requires further testing across settings. The study offers a more integrated basis for research and interventions that address not only screen use itself, but also the structural and relational pressures shaping contemporary parenting.